WATERBIRDS BIODIVERSITY AND ATTENDANCE IN Rhizophora Sp. MANGROVE STANDS OF VARYING PLANTING AGES - Kadarsah, Anang (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2015)
Many species of waterbirds depend on wetland sites and related with variated habitats based on the maturity of ecosystems. The objective of this study was to determine the attendance and biodiversity of waterbirds in Rhizophora sp. mangrove stands of varying planting ages in Subang, West Java. Comparisons were made among five stands of different ages in 4 years, 12 years, 21 years, 29 years, and 38 years. Parameters compared were mangrove structure and waterbirds biodiversity. Structure of mangrove was observed in three plots measuring 10 m x 10 m, while waterbirds abundance was doing by bird watching in the three times of test. Results show that mangrove structure differed among stand ages, except in plant cover physiognomy. Average tree height at the youngest stand (4 years) was 1.56±0.33 meters, DBH 2.92±0.23 cm,, and biomass 1.45 kg m-2 ; whereas at the oldest stand (38 years), average height 8.13±5.65 meters, DBH 16.29±7.23 cm, and biomass 108.62 kg m-2. Sixteen species waterbirdss were recorded found in Rhizophora sp. mangrove stands. Six recorded species are listed as endangered in the IUCN Red List. Occurence of waterbirds shows a variety ranged from eight to thirteen species, with the lowest occurrence at the 4 years stand (9.5%) and highest at 29 years (46.2%). The general conclusion is that age (time) affected certain parameters of mangrove structure, but have no effect to waterbirds attendance. Presence of waterbirds also did not show a clear trend or pattern among stands.Keywords: biodiversity, mangrove, Rhizophora, waterbirds.